Clinical outcomes among pregnant patients with cardiac disease only and those with co-existing pregnancy-associated hypertension - Gupta, Karishma; Shetty, Arthika; Prasad, Madhva; Gupta, Alka S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Impact of cardiac disease on pregnancy is significant. Impact of hypertension on pregnancy is also significant. “Does occurrence of hypertension along with cardiac disease worsen the outcomes?” forms the crux of this study. The aim of the present study was to determine the impact of pregnancy-associated hypertension on the clinical outcomes of pregnant patients with cardiac disease. Methods: Retrospective, observational, comparative, case control study of one and half year duration conducted in a tertiary care referral hospital. The various medical and obstetric parameters were studied and compared. Results: Among 143 patients studied, 36 were hypertensive and 107 were non-hypertensive. Non-severe hypertension was seen in 17%, severe hypertension in 4% and eclampsia in 4%. Average age was 26 years and majority were first or second gravida. Valvular heart disease was the most common cardiac disease encountered. Gestational age at delivery, perinatal outcome and occurrence of pulmonary hypertension were all similar in both the hypertensive and non-hypertensive groups. The most common mode of delivery was vaginal delivery. The cesarean section rate was 29% and was similar among both hypertensive and non-hypertensive groups. Requirement for induction of labor, occurrence of small-for- gestational age among the newborns, intensive care unit admission due to heart failure and maternal death was higher (statistically significant (p<0.05) among the hypertensive group. Conclusions: Presence of hypertension worsens outcomes among pregnant patients with cardiac disease. The coexistence of hypertension and cardiac disease should alert the obstetrician and specialist physician towards a more vigilant management. The findings of this study may help risk stratification (development of pregnancy associated hypertension) while counseling patients with heart disease.